Guanidinium (aqua-2κO)(4-hydroxy-6-carboxypyridine-2-carboxylato-2κ3O2,N,O6)(μ-4-hydroxypyridine-2,6-dicarboxylato-1:2κ4O2,N,O6:O2)(4-hydroxypyridine-2,6-dicarboxylato-1κ3O2,N,O6)dizincate(II) dihydrate - Faranak Manteghi; Mohammad Ghadermazi; Elham Motyeian; Somayeh Saadaty; Hossein Aghabozorg (Acta Crystallographica Section E, 2008)
The title compound, (CH6N3)[Zn2(C7H3NO5)2(C7H4NO5)(H2O)]·2H2O, has an anionic binuclear complex of ZnII balanced with a guanidinium cation. There are two uncoordinated water molecules in the structure. The asymmetric unit of the compound has two different coordination types (the coordination of Zn1 is distorted trigonal-bipyramidal, while that of Zn2 is distorted octahedral) of ZnII in the crystal structure that are bridged to each other via one hypydc2− group (hypydcH2 is 4-hydroxypyridine-2,6-dicarboxylic acid). A variety of intermolecular O—H...O, N—H...O and C—H...O hydrogen bonds involving water molecules, cations and anions, and also a weak π–π interaction [3.798 (1) Å], are responsible for extending the structure into a three-dimensional network.